Design and analysis of current mirror OTA in 45 nm and 90 nm CMOS technology for bio-medical application - Wan Mohammad Ehsan Aiman Wan Jusoh; Siti Hawa Ruslan (Bulletin of Electrical Engineering and Informatics, 2020)
This paper proposed a design and performance analysis of current mirror operational transconductance amplifier (OTA) in 45 nm and 90 nm complementary metal oxide semiconductor (CMOS) technology for bio-medical application. Both OTAs were designed and simulated using Synopsys tools and the simulation results were analysed thoroughly. The OTAs were designed to be implemented in bio-potential signals detection system where the input signals were amplified and filtered according to the specifications. From the comparative analysis of both OTAs, the 45 nm OTA managed to produce open loop gain of 45 dB, with common mode rejection ratio (CMRR) of 93.2 dB. The 45 nm OTA produced only 1.113 μV√Hz of input referred noise at 1 Hz. The 45 nm OTA also consumed only 28.21 nW of power from ± 0.5 V supply. The low-power consumption aspect displayed by 45 nm OTA made it suitable to be implemented in bio-medical application such as bio-potential signals detection system where it can be used to amplify and filter the electrocardiogram (ECG) signals.